Effectiveness of BNT162b2 mRNA COVID-19 vaccine against SARS-CoV-2 variant Beta (B.1.351) among persons identified through contact tracing in Israel: A prospective cohort study. (December 2021) - Singer, Shepherd R.; Angulo, Frederick J.; Swerdlow, David L.; McLaughlin, John M.; Hazan, Itay; Ginish, Netanel; Anis, Emilia; Mendelson, Ella; Mor, Orna; Zuckerman, Neta S; Erster, Oran; Southern, Jo; et al.
Abstract: Background: SARS-CoV-2 variant Beta (B.1.351) was designated as a Variant of Concern (VoC) after becoming the dominant strain in South Africa and spreading internationally. BNT162b2 showed lower levels of neutralizing antibodies against Beta than against other strains raising concerns about effectiveness of vaccines against infections caused by Beta. We estimated BNT162b2 vaccine effectiveness (VE) against Beta infections in Israel, a country with high vaccine uptake. Methods: The Ministry of Health (MoH) identified Beta cases through mandatory reporting of SARS-CoV-2 cases and whole genome sequencing (WGS) of specimens from vaccination-breakthrough infections, reinfections, arriving international travelers, and a selection of other infected persons. A cohort analysis was conducted of exposure events of contacts of primary Beta cases. WGS was conducted on available PCR-positive specimens collected from contacts. VE estimates with 95% confidence intervals (CIs) against confirmed and probable Beta infections were determined by comparing infection risk between unvaccinated and fully-vaccinated (≥7 days after the second dose) contacts, and between unvaccinated and partially-vaccinated (<7 days after the second dose) contacts. Findings: MoH identified 310 Beta cases through Jun 27, 2021. During the study period (Dec 11, 2020 – Mar 25, 2021), 164 non-institutionalized primary Beta cases, with 552 contacts aged ≥16 years, were identified. 343/552 (62%) contacts were interviewed and tested. 71/343 (21%) contacts were PCR-positive. WGS was performed on 7/71 (10%) PCR-positive specimens; all were Beta. Among SARS-CoV-2-infected contacts, 48/71 (68%) were symptomatic, 10/71 (14%) hospitalized, and 2/71 (3%) died. Fully-vaccinated VE against confirmed or probable Beta infections was 72% (95% CI -5 – 97%; p=0·04) and against symptomatic confirmed or probable Beta infections was 100% (95% CI 19 – 100%; p=0·01). There was no evidence of protection in partially-vaccinated contacts. Interpretation: In a prospective observational study, two doses of BNT162b2 were effective against confirmed and probable Beta infections. Through the end of June 2021, introductions of Beta did not interrupt control of the pandemic in Israel. Funding: Israel Ministry of Health and Pfizer.